24 Online learning about death, dying and grief: OpenLearn resources and free education from the open university. (14th March 2023) - ,; Borgstrom, Erica
Abstract : Introduction: Education and training are a core feature of palliative and end of life care policy and practice, both for professionals and the general public. The Open University (OU) has a commitment to providing free educational resources drawing on its expertise in online and distant learning via OpenLearn. Open Thanatology at the OU curate a collection of free death-related materials on this platform to enable education about palliative care, death, dying and grief. Methods: On the OpenLearn platform, we create and provide free open educational resources informed by learning design based on Open University research and curriculum. These include brief articles, animations, videos, interactives, and short courses. The latter are developed from our university-level modules on death, dying and bereavement. We also create content based on collaboration with organisations and public engagement work. The items are provided under creative common licences. Results: As a platform, OpenLearn has over 16 million visits annually. The introductory course on death, dying and bereavement had over 16, 000 unique visits in 2021–2022 with over 4, 000 completing the course; 20% of visitors click to learn more about studying the topic at university level (click-through rate). Animations and interactives received between 300–1000 visitors during that year, with click-through rates between 13–20%. Three core interactives have attracted over 10, 000 learners since their release (between 2018–2021). The Open Thanatology Hub received over 200 unique visits in less than a year with a 23% click-through rate. Several short videos have won film awards. Conclusion: It is possible to create free educational resources about death that can reach wide audiences and that can be reused beyond the OU. Such resources can be vital for professional and public education now and in the future. Typical website data metrics currently does not provide longitudinal information about how this learning impacts thoughts and behaviours. Link to the Open Thanatology Hub: https://www.open.edu/openlearn/health-sports-psychology/open-thanatology-hub